Biomarkers in Post-kala-azar Dermal Leishmaniasis - Zijlstra, Eduard E. (Frontiers in Cellular and Infection Microbiology, 2019)
Post-kala-azar dermal leishmaniasis (PKDL) follows visceral leishmaniasis (VL, kala-azar) in 10–60% of cases. It is characterized by an asymptomatic skin rash, usually starting in the face and consisting of macules, papules, or nodules. Diagnosis is difficult in the field and is often made clinically. There is an extensive differential diagnosis, and parasitological confirmation is preferred particularly when drug treatment is considered. The response to treatment is difficult to assess as this may be slow and lesions take long to heal, thus possibly exposing patients unnecessarily to prolonged drug treatment. Biomarkers are needed; these may be parasitological (from microscopy, PCR), serological (from blood, or from the lesion), immunological (from blood, tissue), pathological (from cytology in a smear, histology in a biopsy), repeated clinical assessment (grading, photography), or combinations. In this paper, we will review evidence for currently used biomarkers and discuss promising developments.